Maṣlaḥah and Its Application in Indonesia Fatwā - Khoiruddin Nasution (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
Many experts of classical Malay literature argues that Persian influence is known very well to the traditional Malay literature. This is evident from a number of Malay literary texts are very popular, such as Saga Bakhtiar, Hikayat Amir Hamzah, Hikayat Muhammad Hanafiyah and a thousand books is a known problem that some sort of adaptation or even a direct translation of Persian texts.DOI: 10.15408/sdi.v3i4.793